Quantifying evapotranspiration from dominant Arctic vegetation types using lysimeters. Issue 1 (26th September 2022) - Clark, Jason A.; Tape, Ken D.; Young‐Robertson, Jessica M.
Abstract: The thermal and hydraulic properties of the moss and organic layer regulate energy fluxes, permafrost stability, and hydrologic function in Arctic tundra. Our goal was to quantify evapotranspiration (ET) from dominant vegetation types in Arctic tundra. We designed and deployed a network of electronic automated weighing micro‐lysimeters ( n  = 58, area = 0.06 m 2 ). We selectively clipped groups of plants from a subset of lysimeters to isolate ET from moss, tussocks, and mixed vascular plants. High rates of evaporation (E) recorded during the study period in the moss E lysimeters (64 mm) and high ET in the tussock ET lysimeters (60 mm) show that mosses and sedge tussocks ( Eriophorum vaginatum ) are the major constituents of local tundra ET. Moss E was consistently higher than ET from mixed vascular species with moss understory indicating that moss E dominates tundra water efflux at sites with moss understory. The ET partitioning presented here will allow for improved prediction of changes in water flux associated with observed and future vegetation change. Future changes in the composition and cover of mosses and vascular plants will not only alter partitioning of tundra ET but may also affect the significant role plants play in the moisture regime and thermodynamics of Arctic permafrost soils.